2021
DOI: 10.46234/ccdcw2021.114
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Outbreak Caused by Contaminated Packaging of Imported Cold-Chain Products — Liaoning Province, China, July 2020

Abstract: What is known about this topic? Few major outbreaks of coronavirus disease 2019 have occurred in China after major nonpharmaceutical interventions and vaccines have been deployed and implemented. However, sporadic outbreaks that had high possibility to be linked to cold chain products were reported in several cities of China.. What is added by this report?In July 2020, a COVID-19 outbreak occurred in Dalian, China. The investigations of this outbreak strongly suggested that the infection source was from COVID… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 11 publications
1
30
0
Order By: Relevance
“…This study also finds other potential transmission between two probable cases regardless of P1 and P2’s connection in C1’s contact network ( Figure 1 ). A previous study in Liaoning Province also showed a phenomenon in an outbreak that made it difficult to determine the first index case, persons who were double-positive for IgM and IgG but negative for nucleic acid testing were also found, which supported our finding ( 10 ).…”
Section: Discussionsupporting
confidence: 90%
“…This study also finds other potential transmission between two probable cases regardless of P1 and P2’s connection in C1’s contact network ( Figure 1 ). A previous study in Liaoning Province also showed a phenomenon in an outbreak that made it difficult to determine the first index case, persons who were double-positive for IgM and IgG but negative for nucleic acid testing were also found, which supported our finding ( 10 ).…”
Section: Discussionsupporting
confidence: 90%
“…A further cluster of cases was reported in July 2020 in Dalian, China, the first of which was in an employee of a cold chain food company 4. No local infections had been reported in Dalian for 111 consecutive days before this case was confirmed.…”
Section: Reported Casesmentioning
confidence: 85%
“…According to the investigations of detailed field epidemiology, all six outbreaks were associated with SARS‐CoV‐2 contaminated imported cold‐chain products exposure. 9 , 10 , 11 , 12 , 13 , 14 The related cold‐chain products importers came from the Europe or North America (Table 1 ). To trace the source of SARS‐CoV‐2 that caused the outbreak, samples were taken from the surface of the initial or index cases associated cold‐chain products each outbreak, and were subjected to SARS‐CoV‐2 specific RT‐PCR testing.…”
Section: Characteristics Of Six Cold‐chain Related Covid‐19 Outbreaks...mentioning
confidence: 99%